Antiphospholipid Sundrome in Childhood Systemic Lupus Erythematosus - Paudyal, B (Journal of Nepal Health Research Council, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Antiphospholipid syndrome is an autoimmune disease that presents with recurrent arteriovenous thrombosis, repeated pregnancy loss and elevated titres of anti phospholipid antibodies in the blood. It is a common cause of acquired thrombosis and can manifest within any part of the vascular tree. Inferior Venacava thrombosis at outset, however, is not a common manifestation of systemic lupus erythematosus associated- antiphospholipid syndrome particularly in children. Here, we present a 14-year old girl who developed antiphospholipid syndrome as a presenting manifestation of systemic lupus erythematosus. Â Key words: antiphospholipid syndrome, thrombosis, systemic lupus erythematosus